Religion in U.S. writing classes: Challenging the conflict narrative - Marzluf, Phillip P. (Universiteit Antwerpen, 2011)
In the United States, composition researchers have consistently depicted First-Year Composition (FYC) teachers' responses to students' faith-based writing in terms of a conflict narrative. According to Goodburn (1998), Lindholm (2000), Perkins (2001), and Vander Lei and Fitzgerald (2007), FYC teachers hold strict secular expectations and reject the religious identity and expression of their fundamentalist Christian students. This study explores this conflict narrative by analyzing how 24 FYC teachers in the Midwestern United States describe their own religious identities as well as those of their institutions and respond to two faith-based student texts. The study results challenge simplistic depictions of the conflict narrative. The religious affiliations of the FYC teachers coincide with national averages and neither relate to how teachers described the religious environment of their institutions nor the grades the teachers gave the faith-based texts. Furthermore, rhetorical variables such as genre and audience awareness affect teachers' responses to faith-based writing. Composition researchers, this study concludes, need to complicate how they depict situations in which students express their religious identity within secular post-secondary institutions.
Keywords: Religion; pedagogy; teacher-student; fundamentalism; First-year composition; Faith